Strength Reduction Factor of Steel Frames with Stainless-Steel Braces - Yu Ding; Yan Shi; Hongguo Qin; Xuexin Wang (Buildings)
Previous studies on the strength reduction factor (SRF) have primarily focused on structures without braces or with traditional mild steel braces. However, due to the corrosion damage affecting braces, the existing research cannot guide the application of damage control concepts in corrosive environments. In contrast, stainless-steel braces provide a new direction for applying damage control due to their excellent corrosion resistance. This paper investigates the SRF of steel frames with stainless-steel braces to fill this gap. An equivalent single-degree-of-freedom (SDOF) dual system was established, with a steel frame and a stainless-steel brace in parallel, by simulating the nonlinear mechanical behavior of the stainless-steel braces using the Ramberg–Osgood (R-O) hysteresis model. A corresponding procedure for calculating the SRF spectra was developed. The effects of the displacement ductility factor, site conditions, R-O hysteresis model parameter, and fuse control parameters were statistically analyzed. The results show that the stainless-steel braces could significantly improve the SRF of the braced steel frame, enhancing its structural strength reserve, with the R-O hysteresis model parameter suggesting a particularly significant impact (up to 18%). Finally, a predictive model of the R-μ-T-n-α-β relationship was developed, providing a computational tool for the seismic design of braced steel frames in corrosive environments.